2003
DOI: 10.1002/bsl.566
|View full text |Cite
|
Sign up to set email alerts
|

Citizen coping with community notification of released sex offenders

Abstract: The current study investigated citizen reactions to notifications of sex offenders in the neighborhood, in an effort to determine whether sex offender notification laws are accomplishing their goal of increased protective actions against sex offenses. Lazarus's stress and coping theory provided the theoretical framework for the study. Telephone surveys were conducted with 250 Alabama residents who were notified of an offender in the neighborhood. Questions were posed regarding notification importance, fear of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 29 publications
4
71
1
2
Order By: Relevance
“…The majority of 193 individuals surveyed in Florida indicated that they believe that most sex offenders will reoffend and therefore community residents should be told about all sex offenders living amongst them . Though this data suggests that concerned citizens feel safer as a result of knowing where sex offenders live, other surveys have found that notification can increase anxiety because few strategies are concurrently offered for protecting oneself from sex offenders (Caputo, 2001;Caputo & Brodsky, 2004;Zevitz et al, 2000b;Zevitz, 2004). A large majority of mental health professionals have expressed doubt that registration and notification can be successful in preventing child sexual abuse, and even speculated that such laws create a false sense of security for parents (Malesky & Keim, 2001).…”
Section: Public Perceptionsmentioning
confidence: 90%
“…The majority of 193 individuals surveyed in Florida indicated that they believe that most sex offenders will reoffend and therefore community residents should be told about all sex offenders living amongst them . Though this data suggests that concerned citizens feel safer as a result of knowing where sex offenders live, other surveys have found that notification can increase anxiety because few strategies are concurrently offered for protecting oneself from sex offenders (Caputo, 2001;Caputo & Brodsky, 2004;Zevitz et al, 2000b;Zevitz, 2004). A large majority of mental health professionals have expressed doubt that registration and notification can be successful in preventing child sexual abuse, and even speculated that such laws create a false sense of security for parents (Malesky & Keim, 2001).…”
Section: Public Perceptionsmentioning
confidence: 90%
“…Through telephone surveys with 250 Alabama residents, Caputo and Brodsky (2004) investigated public reactions to sex offender registration and community notification. Residents who interpreted community notification as important reported using a greater number of coping strategies to deal with the close presence of sex offenders and reported being more fearful of general victimization, personal victimization, and sexual victimization.…”
Section: Information Utilization and Awareness Of Sex Offendersmentioning
confidence: 99%
“…Once the presence of the offender is known it creates unease in the surrounding areas (Anderson & Sample, 2008;Beck & Travis, 2004;Brown et al, 2008;Caputo & Brodsky, 2004;Craun & Theriot, 2009;Levenson et al, 2007a;Lieb & Nunlist, 2008;Phillips, 1998;Zevitz, 2004;Zevitz & Farkas, 2000a).…”
Section: Nexus Of the Rso-home Sale Value Research To The Awareness Omentioning
confidence: 99%
“…The mere presence of a convicted sex offender or offenders inspires increased amounts of anxiety, fear, and concern for general safety among community members (Anderson & Sample, 2008;Beck & Travis, 2004;Brown et al, 2008;Caputo & Brodsky, 2004;Craun & Theriot, 2009;Levenson et al, 2007a;Lieb & Nunlist, 2008;Phillips, 1998;Zevitz, 2004;Zevitz & Farkas, 2000a). Regarding fear, roughly one-third (38%) of Zevitz and Farkas' (2000a) sample of Wisconsin residents who attended community notification meetings designed to increase sex offender awareness reported an increase in fear.…”
Section: Non-urban Communitiesmentioning
confidence: 99%
See 1 more Smart Citation